PKM Pelatihan Aplikasi Computer Aided Design (CAD) Pada Siswa SMK di Kabupaten Majene - Moeh. Kay Muddin Asnur; Mohammad Junaedy Rahman; M. Reza Hasrul; Furqan Ali Yusuf; Tri Amarta Wiranata (PT. Global Research Collaboration, 2024)
One of the essential skills in the industry 4.0 era is the use of Computer Aided Design (CAD) software, which enables the creation of two-dimensional (2D) and threedimensional (3D) designs across various industrial fields. This study aims to enhance the CAD skills of vocational high school (SMK) students in Kabupaten Majene through a training program. Using a quasi-experimental method and a pre-test and post-test design, the two-day training showed significant improvements in students' skills. The average post-test score increased from 55 to 75, and the number of students scoring above 70 rose from 6 to 18. These results are consistent with previous research indicating that CAD training effectively improves students' competencies. The program is expected to address challenges faced by SMKs, particularly regarding limited facilities and skilled teachers, and to enhance the job readiness of SMK graduates in Kabupaten Majene. Recommendations include improving computer facilities, providing ongoing training for teachers, and integrating a curriculum that aligns with industry needs. Vocational high schools (SMK) play a critical role in preparing graduates for the workforce in the industrial sector.